2014
DOI: 10.1371/journal.pone.0105695
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of the Simple Clinical Score and the HOTEL Score, Two Scores for Predicting Short-Term Mortality after Admission to an Acute Medical Unit

Abstract: BackgroundClinical scores can be of aid to predict early mortality after admission to a medical admission unit. A developed scoring system needs to be externally validated to minimise the risk of the discriminatory power and calibration to be falsely elevated. We performed the present study with the objective of validating the Simple Clinical Score (SCS) and the HOTEL score, two existing risk stratification systems that predict mortality for medical patients based solely on clinical information, but not only v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…To our surprise, we found that functional status [ 39 ], such as mobility and nutrition[ 40 ] were of major importance. Reduced mobility has recently also been included in the Simple Clinical Score for medical emergency patients in addition to vital signs [ 25 ]. Both poor nutrition and reduced mobility could be consequences of the disease process, but they may have health-related effects of their own.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our surprise, we found that functional status [ 39 ], such as mobility and nutrition[ 40 ] were of major importance. Reduced mobility has recently also been included in the Simple Clinical Score for medical emergency patients in addition to vital signs [ 25 ]. Both poor nutrition and reduced mobility could be consequences of the disease process, but they may have health-related effects of their own.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic models for acute care situations always include either several vital signs typically obtained from monitors, electrocardiograms or imaging information, biomarker or procedural characteristics. This information is missing in a large proportion of patients even in medical emergency departments [ 25 ]. There is no prognostic model quantifying the risk in the population of hospitalised patients as a whole—excluding ICU-patients—by a single scoring system.…”
Section: Introductionmentioning
confidence: 99%
“…8 The fraction of irreversibly ill patients in the populations identified by these end points underlines this problem, as seen in studies from the United Kingdom (UK). Such a problem could become increasingly important with the development of more and more accurate models with c-statistics even higher than ViEWS, such as the c-statistic of 0.96 (0.93-0.99) found in a recent Danish validation study of the Simple Clinical Score.…”
Section: Discussionmentioning
confidence: 96%
“…Such a problem could become increasingly important with the development of more and more accurate models with c-statistics even higher than ViEWS, such as the c-statistic of 0.96 (0.93-0.99) found in a recent Danish validation study of the Simple Clinical Score. 8 The fraction of irreversibly ill patients in the populations identified by these end points underlines this problem, as seen in studies from the United Kingdom (UK). A review of 1000 deaths in UK hospitals reported 5.2% of the deaths as having a 50% or greater chance of being preventable.…”
Section: Discussionmentioning
confidence: 96%
“…The AUCs of the ROC analysis models for 30‐day mortality using PANDORA scores were reported to be between 0.79 and 0.82. It is worth noting that ICU patients were excluded in the development of the PANDORA score because the authors noted several “good” (as defined by AUCs in the 0.8–0.9 range) mortality prediction tools validated for use in the ICU . Indeed, widely used ICU‐related mortality prediction scores, such as APACHE, SOFA, Mortality Probability Model, and Simplified Acute Physiology scores, all require extensive physiologic data and may require at least 24 hours of care before they can be calculated .…”
Section: Discussionmentioning
confidence: 99%